2019
DOI: 10.1093/bmb/ldz024
|View full text |Cite
|
Sign up to set email alerts
|

The counter-intuitive role of the neutrophil in the acute respiratory distress syndrome

Abstract: Introduction Neutrophils are the primary effectors of the innate immune system but are profoundly histotoxic cells. The acute respiratory distress syndrome (ARDS) is considered to be a prime example of neutrophil-mediated tissue injury. Sources of data The information presented in this review is acquired from the published neutrophil cell biology literature and the longstanding interest of the senior authors in ARDS pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 73 publications
5
37
0
Order By: Relevance
“…Neutrophils sequestered in the lung rapidly accumulate in the alveolar space where gas exchange is substantially impaired due to oedema and alveolar collapse. Here, excessive neutrophil activation, including the degranulation of histotoxic proteins and pro-inflammatory cytokines, propagate diffuse host lung damage with high mortality [125]. In a murine model of hypoxia-induced acute lung injury, abrogation of hypoxic neutrophil survival by treatment with intra-tracheal IL-4 was able to promote resolution of inflammation and resulted in reduced bronchoalveolar lavage NE content, although the direct effect of IL-4 on degranulation was not assessed in this study [126].…”
Section: Hypoxia-enhanced Neutrophil Degranulation Can Damage Host Timentioning
confidence: 76%
“…Neutrophils sequestered in the lung rapidly accumulate in the alveolar space where gas exchange is substantially impaired due to oedema and alveolar collapse. Here, excessive neutrophil activation, including the degranulation of histotoxic proteins and pro-inflammatory cytokines, propagate diffuse host lung damage with high mortality [125]. In a murine model of hypoxia-induced acute lung injury, abrogation of hypoxic neutrophil survival by treatment with intra-tracheal IL-4 was able to promote resolution of inflammation and resulted in reduced bronchoalveolar lavage NE content, although the direct effect of IL-4 on degranulation was not assessed in this study [126].…”
Section: Hypoxia-enhanced Neutrophil Degranulation Can Damage Host Timentioning
confidence: 76%
“…The recent clinical trial (conducted prior to the onset of the COVID-19 pandemic) showed correlation between the NETs content and severity of the community-acquired pneumonia [ 92 ]. Acute lung injury (ALI) and ARDS of various etiologies are accompanied by excessive NETosis (see review [ 93 ]). NETs in these pathologies may be involved in the damage of alveolar epithelium and endothelium.…”
Section: The Role Of Netosis In Host Defence and Pathologymentioning
confidence: 99%
“…Recombinant DNase I has been successfully used in almost all models of pathologies associated with NETosis. In particular, introduction of DNase I significantly facilitates the course of ARDS [ 93 ] and COPD [ 94 ] in animal models. In patients with cystic fibrosis, DNase inhalation improved lung function, and neutrophil elastase facilitated sputum dissolution making it more accessible for DNase [ 110 ].…”
Section: Therapy Of Netosismentioning
confidence: 99%
“…These chemoattractive signals are recognized by local immune cells, which produce inflammatory mediators that further boost neutrophil recruitment. In ARDS, endothelial cells activate and capture circulating neutrophils [ 31 , 32 ]. Neutrophils are sequestered through selectin-mediated binding, triggering “inside-out” activation of integrins, such as CD11a/CD18, which binds to intercellular adhesion molecules (ICAMs) from the endothelium [ 33 ].…”
Section: Role Of Neutrophils In Ardsmentioning
confidence: 99%